A Robust [K,KL] Sector for Nonlinear System - Sachan A.; Kamal S.; Yu X.; Singh D.; Xiong X. (My University, 2025)
This brief suggests an approach to design a robust {[\mathcal {K,KL}]} sector for nonlinear system subjected to parametric/model uncertainty and this design relies on the Matrosov's results. The nonlinear surface to decide the boundaries of a sector is designed by using a control-Lyapunov function. Here, a Hands-Off control consists of constant and state-dependent gain is used to force the state vectors to the interior of robust {[\mathcal {K,KL}]} sector and shows asymptotic stability with minimum support to the nonlinear system by avoiding the redundant control effort. The usefulness of the proposed design is illustrated by a nonlinear electronic circuit. © 2004-2012 IEEE.